Agri-Nanotechnology and Tree Nanobionics: Augmentation in Crop Yield, Biosafety, and Biomass Accumulation - Abbas, Manzar; Yan, Kuan; Li, Jia; Zafar, Sara; Hasnain, Zuhair; Aslam, Nazia; Iqbal, Naeem; Hussain, Syed Sarfaraz; Usman, Muhammad; Abbas, Mubashir; Tahir, Muhammad; Abbas, Sammar; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanomaterials (NMs) are the leading edge as an amazing class of materials that consists of at least one dimension in the range of 1–100 nm. NMs can be made with exceptional magnetic, electrical, and catalytic properties different from their bulk counterparts. We summarized unique features of NMs, their synthesis, and advances in agri-nanotechnology and cutting-edge nanobionics. The review describes advances in NMs including their applications, dosimetry to ensure biosafety, remote sensing of agro-forestry fields, nanofertilizers, and nanopesticides, and avoid post-harvest losses, gene delivery, and nanobionics. Tree nanobionics has enabled the synthesis and delivery of nanosensors, which enhance the rate of photosynthesis, detection of pathogens, and poisonous residues to ensure biosafety and biomass accumulation. Finally, we conclude by discussing challenges, future perspectives, and agro-ecological risks of using NMs.